Models of generalized anxiety disorder: does the emotion dysregulation model aid understanding? - Deleurme, Kendall A. (My University, 2017)
While models of generalized anxiety disorder (GAD) are available, the literature continues to explore and expand upon the different conceptualizations. Among these models, one of the most recent is the Emotion Dysregulation Model (EDM). According to the EDM, individuals with GAD have issues understanding, expressing, and managing emotions. The EDM proposes that individuals with GAD experience the following: emotional hyperarousal, involving low emotional thresholds; poor understanding of emotions, including problems with describing and labelling; negative attitudes towards emotions; and unsuccessful emotion regulation and management strategies. However, there is a lack of research providing support for the utility of the EDM. Furthermore, a gap exists in the literature comparing the EDM to more established models. The proposed study extends the current literature by examining whether the EDM helps explain GAD symptoms when compared to a well-established model of GAD, the Metacognitive Model (MCM). The MCM emphasizes that individuals with GAD have negative beliefs about the dangerousness and uncontrollability of worry. Several self-report measures previously used in research of the EDM and the MCM will be administered to non-clinical university participants (N = 400) to investigate which measures uniquely predict GAD symptoms. The proposed study hypothesizes the following: GAD symptoms will positively correlate with emotion dysregulation; GAD symptoms will positively correlate with negative beliefs about worry; and emotion dysregulation will predict GAD symptoms independent of negative beliefs about worry. Expected findings have implications for treatment of GAD, encouraging an approach focusing on emotion psychoeducation and development of effective emotional regulation strategies.
Presented on April 24, 2017 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: generalized anxiety disorder; emotions